An overview of a systems model of cassava pests in Africa - Gutiérrez, A.P.; Wermelinger, B.; Schulthess, F.; Baumgaertner, J.U.; Yaninek, John S.; Herren, H.R.; Neuenschwander, Peter; Löhr, Bernhard; Hammond, W.N.O.; Ellis, C.K. (Springer, 1987)
A systems model is described for cassava, Manihot esculenta Crantz, two of its introduced herbivores, the cassava green mite (CGM), Mononychellus tanajoa (Bondar), sensu lato, and the cassava mealybug (CM), Phenacoccus manihoti Mat.-Ferr., the introduced CM parasitoid, Epidinocarsis lopezi (DeSantis) and coccinellid predator of the genus Hyperaspis. The systems model includes the effects of weather, soil nitrogen and water levels on the interactions of the system’s components.